Characterization, Enzymatic Activity, and Secondary Metabolites of Fungal Isolates from Lake Sonachi in Kenya - Ndwigah, Ireri F.; Bogai, Hamadi I.; Wanyoike, Wanjiru; Mwirichia, Romano K. (My University, 2015)
The soda lakes of Kenya provide an extreme environment where diverse groups of microorganisms thrive. They are characterized by great variation in temperature, halophillic and alkaliphilic- extreme conditions. Lake Sonachi has been the study site for this research. The study sort to isolate, characterize and identify fungi, screen for potential exo-enzymes and secondary metabolites production that may be of industrial application. Malt extract agar was used in the isolation of fungi and six (6) isolates were recovered. Inhibition zones were used to measure the enzymatic and antimicrobial activity of the isolates. GC-MC analysis was done on the filtrates extracted from the fungi to identify secondary metabolites. Molecular characterization of the 18s rDNA was done using fungal primers and sequencing PCR products.s .Phylogenetic tree was inferred using neighbor- joining method. The fungal isolates were alighned to diferrent genera, Acrimonies sp., Scopulariopsissp, Verticilium sp. Fusariumsp and Paecilomyces sp. The fungal isolates produce different types of enzymes (cellulases, proteases, pectinases and lipases) and metabolites (acids, ketones, quinones, alcohols, esters etc) .Antimicrobial assay showed that most of the fungal isolates produced inhibition zones ranging from 0.1 to 4mm, an indication of presence of compounds with antimicrobial activity against most of the test organisms, E.coli, B. subtilis, S.aureasetc, used in this study. Results indicate that Lake Sonachi, a soda lake has fungal species that are capable of producing enzymes and metabolites with antimicrobial activity.
Keywords: Characterization; Enzymatic activity; Antimicrobial activity; Secondary metabolite